Disturbances of carbohydrate metabolism in patients with endocrine diseases - Karnafel, Waldemar (Przewodnik Lekarza/Guide for GPs, 2005)
In endocrinopathies with hipersecretion of growth hormon, glucagon, glucosteroids and katecholamines we can observe also prediabetes and diabetes mellitus. After successfull treatment of endocrine disease we observe the normalization of carbohydrate metabolism.